(3cJGH GdJUQja aj GdGOhjI GdeQcHIs - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s ((3OGQ GdTaGA HeUQ GdeMQhSI s)
(3ChdgG (B:s
(3GdebGdI GdKGefI hGdYTQhf ef cJGH GdJUQja ddRgQGhi ai EUdGM GdCOhjI deG LeYJ gPG GdcJGH GdYXje GdaGFOI SejJg HcJGH GdJUQja ai GdGOhjI GdeQcHI s
(3BNQgG (B:s
(3hJQaYg Edi hbJ MGLJc hEf CQOJ Cf Jchf GdUMjaI UMjMI aCWdgG HTF ef Wjf GdUdUGd JeJ GdebGdI GdKGefI hGdYTQhf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3GdebGdI GdKGefI hGdYTQhf ef GdcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
Keywords: (3GdWHs